Starch - Hoover, Jessie May (My University, 1905)
Introduction: Starch is a carbohydrate of complex composition having the formula (C6H10O5)n. The value of n is unknown but may be anything from 2 to 200. Because of the wide distribution of starch it is one of the most universally used foods, and occurs in almost all living plants - tubers, seeds, roots, green fruits, tree trunks, and in fact, in some part of every chlorophyll bearing plant at some time during its existence. Fungi do not contain it. Rice is one of the common starchy foods. It is estimated that about two thirds the earth's population obtain their food from rice, this is true especially of the Orientals. Those who live along the sea coast or near rivers have the fish to furnish some proteid variety and so become less weary of the monotonous diet. The people of tropical countries find bananas a very wholesome and nutritious form of carbohydrate food. Corn and wheat furnish two very common sources of starchy food in the United States. The uses of starch are varied as food for animals is not its only use. The starch in the seed or tuber is placed there in order that the young and growing plant may have nourishment at once. These seeds contain ferments which acting upon the starch reduce it to maltose and from maltose to dextrose, which is soluble and assimilable by the plant. Sometimes wheat flour will not make good bread even when the greatest care is exercised, this is often due to the fact that the starch has already been converted to the simpler sugars by the enzyme or ferment present so when the yeast is added alcoholic fermentation sets up at once followed by acid fermentation and we have sour bread if the process is long continued.
Citation: Hoover, Jessie May. Starch. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Starches are Universal Food; Soluble Dextrins or Maltose; Amylopsin; Theses